Factors Leading to Transmission Risk of Acinetobacter baumannii*. Issue 7 (July 2017) - Thom, Kerri A.; Rock, Clare; Jackson, Sarah S.; Johnson, J. Kristie; Srinivasan, Arjun; Magder, Laurence S.; Roghmann, Mary-Claire; Bonomo, Robert A.; Harris, Anthony D.
Abstract : Objectives: To identify patient and healthcare worker factors associated with transmission risk of Acinetobacter baumannii during patient care. Design: Prospective cohort study. Setting: ICUs at a tertiary care medical center. Patients: Adult ICU patients known to be infected or colonized with A. baumannii . Measurements and Main Results: Cultures of skin, respiratory tract, and the perianal area were obtained from participants and evaluated for the presence of A. baumannii . Healthcare worker-patient interactions were observed (up to five interactions/patient) and activities were recorded. Healthcare worker hands/gloves were sampled at room exit (prior to hand hygiene or glove removal) and then evaluated for the presence of A. baumannii . Two hundred fifty-four healthcare worker-patient interactions were observed among 52 patients; A. baumannii was identified from healthcare worker hands or gloves in 77 (30%) interactions. In multivariate analysis, multidrug-resistant A. baumannii (odds ratio, 4.78; 95% CI, 2.14–18.45) and specific healthcare worker activities (touching the bed rail [odds ratio, 2.19; 95% CI, 1.00–4.82], performing a wound dressing [odds ratio, 8.35; 95% CI, 2.07–33.63] and interacting with the endotracheal tube or tracheotomy site [odds ratio, 5.15; 95% CI, 2.10–12.60]), were associated with hand/glove contamination. Conclusions: Healthcare worker hands/gloves are frequently contaminated with A. baumannii after patient care. Patient-level factors were not associated with an increased transmission risk; however, having multidrug-resistant- A. baumannii and specific healthcare worker activities led to an increased contamination risk. Our findings reveal a potential selective advantage possessed by multidrug-resistant- A. baumannii in this environment and suggest possible areas for future research.